The Phytochemical Profile and Antioxidant and Gastroprotective Effects of Three Varieties of Chenopodium quinoa Willd. Sprouts Cultivated in Peru - Edwin Carlos Enciso-Roca; Jorge Luis Arroyo-Acevedo; Pablo Williams Común-Ventura; Johnny Aldo Tinco-Jayo; Enrique Javier Aguilar-Felices; Mahomi Bertha Ramos-Meneses; Rosa Elizabeth Carrera-Palao; Oscar Herrera-Calderon (Scientia Pharmaceutica)
Chenopodium quinoa sprouts possess a superior nutritional profile relative to conventional quinoa seeds, which is mainly attributable to their germination process. Sprouting quinoa is able to preserve its substantial nutritional value while enhancing its bioavailability and digestibility. The aim of this study was to evaluate the gastroprotective effects of hydroalcoholic extracts of three varieties of quinoa sprouts (pasankalla, yellow maranganí, and black coito). The chemical compounds were determined using LC-MS (Liquid Chromatography–Mass Spectrometry). Antioxidant activity was determined using two analytical methods, 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). To evaluate the gastroprotective effects of these hydroalcoholic extracts in Holtzman male rats, a gastric lesion was induced with 96% ethanol after the administration of the hydroalcoholic extract of the three varieties of C. quinoa sprouts. Our phytochemical analysis results reveal the presence of amino acids (valine, leucine, isoleucine, phenylalanine, tryptophane, proline, tyrosine, and arginine, among others) and their derivatives, organic acids, monosaccharides, lipids, nucleobases/nucleosides, steroids, triterpene saponins, and coumarins. The pasankalla, yellow maranganí, and black coito varieties exhibited antioxidant capacities of 36.70, 32.32, and 34.63 µmol Trolox equivalent (TE)/mg of extract for the DPPH radical and 56.61, 41.56, and 52.09 µmol TE/mg of extract for the ABTS radical, respectively. The percentage of antisecretory efficiency at a dose of 500 mg/kg for the pasankalla, yellow maranganí, and black coito varieties was 34.13%, 30.67%, and 26.67%, respectively, and the anti-ulcer effect, expressed as a percentage of inhibition of ulcer formation, was 74.7%, 67.4%, and 69.5%, respectively. In contrast, the groups treated with ranitidine and sucralfate exhibited percentages of 59.0% and 67.4%, respectively. The pasankalla quinoa exhibits more significant antioxidant activity and a stronger gastroprotective effect compared to the other varieties examined in this study. In conclusion, the hydroalcoholic extracts of the three varieties of C. quinoa sprouts exhibited a gastroprotective effect, and the pasankalla variety at a dose of 500 mg/kg exhibited a stronger protective effect on the gastric mucosa of the rats.